Computational insights into electrochemical cross‐coupling of quaternary borate salts. Issue 1 (3rd May 2021) - Matz, Florian; Music, Arif; Didier, Dorian; Jagau, Thomas‐C.
Abstract: Cross‐coupling reactions for C–C bond formation represent a cornerstone of organic synthesis. In most cases, they make use of transition metals, which has several downsides. Recently, metal‐free alternatives relying on electrochemistry have gained interest. One example of such a reaction is the oxidation of tetraorganoborate salts that initiates aryl–aryl and aryl–alkenyl couplings with promising selectivities. This work investigates the mechanism of this reaction computationally using density functional and coupled‐cluster theory. The calculations reveal a distinct difference between aryl–alkenyl and aryl–aryl couplings: While C–C bond formation occurs irreversibly and without an energy barrier if an alkenyl residue is involved, many intermediates can be identified in aryl–aryl couplings. In the latter case, intramolecular transitions between reaction paths leading to different products are possible. Based on the energy differences between these intermediates, a kinetic model to estimate product distributions for aryl–aryl couplings is developed.